From Heritage to Identity: The Role of City Authenticity in Shaping Local Community Identity and Cultural Preservation - Eko Nursanty; Djudjun Rusmiatmoko; Muhammad Fahd Diyar Husni (ARCHIHUMANUM, 2023)
This comprehensive study aims to investigate the role of urban heritage authenticity in shaping citizen identity, with a specific focus on historic cities. By examining the relationship between the perceived authenticity of urban heritage and citizen identity, this research sheds light on the significance of authenticity in interpreting cities' historical evolution and identity. The study employs a three-dimensional measure of urban identity, encompassing cognitive, affective, and evaluative aspects, to establish a connection between urban identity and citizen participation in local initiatives through personal and social norms. To comprehensively explore the impact of city authenticity on citizen identity formation, the research utilises a combination of survey questionnaires, interviews, and document analysis. Three prominent historic cities also serve as case studies: Kampung Kauman in Surakarta, Kampung Laweyan in Surakarta, and Kampung Trusmi in Cirebon. This study contributes to our comprehensive understanding of the role of urban heritage authenticity in shaping citizen identity. The research emphasises the significance of authenticity in interpreting the historical evolution and identity of cities, showcasing its influence on citizens' perceptions, engagement in local initiatives, and overall sense of place. The case studies are practical examples of how authenticity fosters community identity and cultural heritage preservation. The findings of this study provide valuable insights for urban planners, policymakers, and community stakeholders, guiding their efforts to promote and preserve the authentic character of historic cities.